Inoculation, colonization, and distribution of fungal endophytes in Musa tissue culture plants - Paparu, P.; Dubois, T.; Gold, Cliford S.; Adipala, E.; Niere, B.; Coyne, D. (2004)
The use of mutualistic fungal endophytes to control the banana weevil (Cosmopolites sordidus) and banana parasitic nematodes (Radopholus similis, Pratylenchus goodeyi and Helicotylenchus multicinctus) is currently being investigated at the International Institute of Tropical Agriculture. Fungal endophytes are microorganisms that colonize the plant through the root system and for a part or whole of their life cycle live symptomlessly within the plant. Such organisms in some instances have been known to act as antagonists against pests and diseases. For an endophyte strain to be a good antagonist against target pests, it must be present in the plant tissues at the time the plants are attacked by the pests. They therefore need to be artificially inoculated in tissue culture banana plants, must occur at high frequencies in the plant and be able to persist in the plant after inoculation. It is also critical that an endophyte successfully colonizes and persists from the time of inoculation onwards. Screen house studies where two Fusarium oxysporum strains, V2w2 and III4w1, were artificially inoculated into two banana cultivars, Nabusa and Kibuzi (Musa, AAA-EA), using different inoculation methods revealed that tissue colonization depended on the method of endophyte inoculation and differed for the different tissues investigated. Studies using the same two strains and same banana cultivars showed that colonization persistence also depended on inoculation methods and was different among the types of tissue within the banana plant. Plant tissue colonization varied by cultivar and strain combinations, indicating the need for identifying suitable cultivar-strain combinations.